Ultrasound clinics : Reuven Achiron [and twenty others]. - Achiron, Reuven; Andreotti, Rochelle F.;Betel, Carrie B.;Coley, Brian D.;Dighe, Manjiri K.;Dubinsky, Theodore J.;Fleischer, Arthur;Glanc, Phyllis (Philadelphia, Pennsylvania : Saunders, 2012)
The application of ultrasound technology to obstetric and gynacologic issues figures as one of the staples of this imaging modality. This issue features the following articles: Demystifying Ovarian Cysts; Fetal Measurements and Anatomy; Fetal Echocardiography; Management of Threatened Miscarriage; and, Gestational Trophoblastic Diseases.
Includes bibliographical references and index.
Keywords: DIAGNOSTIC ULTRASONIC IMAGING